Strategies in Biologic Augmentation of Rotator Cuff Repair: A Review - Cheung, Emilie V. (Springer-Verlag, 2010)
BACKGROUND: Degenerative rotator cuff tears are increasing with the aging population, and healing is not uniform after surgery. Rotator cuffs may show improved healing when biologic factors are added during surgery. QUESTIONS/PURPOSES: We asked: (1) What cellular processes are involved in normal bone-to-tendon healing? (2) What approaches are being developed in tendon augmentation? (3) What approaches are being developed with the addition of growth factors? METHODS: We reviewed research in relating to biologic augmentation and cellular processes involved in rotator cuff repair, focusing on animal models of rotator cuff repair and nonrandomized human trials. RESULTS: Regular bone-to-tendon healing forms a fibrous junction between tendon and bone that is distinct from the original bone-to-tendon junction. Tendon augmentation with cellular components serves as scaffolding for fibroblastic cells and a possible source of growth factors and fibroblastic cells. Extracellular matrices provide a scaffold for incoming fibroblastic cells, although current research does not conclusively confirm which if any of these scaffolds enhance repair owing in part to intermanufacturer variations and the limited human research. Growth factors and platelet-rich-plasma are established in other fields of research and may enhance repair but have not been rigorously tested. CONCLUSIONS: There is potential application of biologic augmentation to improve healing after rotator cuff repair. However, research in this field is still inconclusive and has not been sufficiently demonstrated to merit regular clinical use. Future human trials can elucidate the use of biologic augmentation in rotator cuff repairs.